Effect of long-acting supplementary local anesthetic on intra and post operative pain in single visit root canal treatment: a randomized control trial - Rao, Apeksha; Anithakumari, R.; Khan, Nida (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Patients often experience varying degrees of pain during or after root canal therapy. This study aimed to assess the effectiveness of long-acting local anesthetics, specifically Ropivacaine, in preventing intra and postoperative pain associated with endodontic treatment compared to lignocaine. Methods: This double-blind, randomised clinical trial included 60 patients with single-rooted mandibular pre-molar teeth. Patients were divided into three groups: Group 1 received lignocaine as an inferior alveolar nerve block, Group 2 received lignocaine as an inferior alveolar nerve block with supplementary intraligamentary lignocaine, and Group 3 received lignocaine as an inferior alveolar nerve block with supplementary intraligamentary Ropivacaine. Pain levels were assessed using the visual analogue scale (VAS) before treatment, during treatment, and at 2, 6-, 12-, 24-, and 48-hours post-treatment. Statistical analysis included mean, standard deviation, Kruskal Wallis Test, Dunn's posthoc test, Chi-square, and Friedman’s test followed by Wilcoxon signed rank post hoc test. Results: Ropivacaine as a supplementary intraligamentary anesthetic significantly reduced intraoperative pain levels at working length (p<0.001) compared to lignocaine used alone or with supplementary intraligamentary lignocaine. Group 3 exhibited statistically significant differences in postoperative pain levels at 12-hour intervals (p<0.001), correlating with reduced intake of oral analgesics (p=0.02). Conclusions: A single dose of 0.2 ml of 0.5% Ropivacaine as a supplementary intraligamentary anaesthetic may be more effective in reducing or preventing intraoperative and post-operative endodontic pain compared to lignocaine, irrespective of the technique used.